THE ROLE OF UMAR IBN ABDULAZIZ IN THE DEVELOPMENT OF ISLAMIC LAW (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the jurisprudential school of Umar ibn Abdulaziz ibnMarwan ibn Hakam (61–101 AH / 681–720 CE), his method of ijtihad, his connectionwith the scholarly heritage of the Companions and Followers (tabiʿun), his experiencein the practical application of Islamic jurisprudence, and his place in the history ofIslamic law. Known not only as a just ruler but also as an ascetic scholar and one ofthe mujtahid scholars, his jurisprudential views formed under the decisive influence ofthe school of the scholars of Medina exercised a profound impact on subsequent Hijaziand Sunni legal thought, particularly the Maliki madhhab. The article examines hisprincipal reforms in state administration the restoration of unjustly seized property, theabolition of unfair taxation, judicial independence, and the formal initiation of hadithcollection and situates each within the framework of Islamic jurisprudential principles.It further analyzes his relationship with the four principal Sunni madhhabs and hisascetic spiritual legacy
Keywords: Umar ibn Abdulaziz; ijtihad; madhhab; tabiʿun; history of jurisprudence; Sunnah; justice; hadith collection; Maliki school; Islamic law.